Barriers for implementing an intervention for substance using adolescents when adding a parent component - Martínez Martínez, Kalina Isela; Contreras-Pérez, María Eugenia; Wagner, Eric F. (Gaceta Médica de Caracas, 2021)
Research has shown that an intervention process with adolescents involving the parents may achieve better results since the interaction with the parents is a protective factor itself. The brief intervention program for adolescents starting substance use is an intervention used in Mexican clinical centers with adolescents who have experienced problems with their substance use but do not present dependency symptoms. The family context is key to the genesis and progression of behavior problems, including substance use, among children and adolescents. An intervention process that involves parents may achieve better results in preventing substance use problems in adolescents